The Value Transformation of Betty Warren in Mona Lisa Smile - Alyni Tjunarwi; Dwi Setiawan (Kata Kita: Journal of Language, Literature, and Teaching, 2013)
This study analyzes a movie entitled Mona Lisa Smile. It is interesting that the movie contains the message about women’s liberation movement reflected through the value transformation done by one of the characters, Betty Warren, which is why we decided to emphasize on the transformation as our main focus. We attempt to reveal the process of Betty Warren’s value transformation by applying two concepts, which are the concept of Angel in the House and the concept of New Woman. We find out that Warren’s experience of value transformation goes through several stages, which are from believing in her old values, going against the new modern values, finding disappointment toward her old values, then having a conflict within herself, and as the result, starting to consider and absorb the new values. The analysis leads to the fact that patriarchal values can be so strong because sometimes, women themselves are subconsciously acting as the agents.